Optimization of convective drying conditions for pomegranate slices based on bioactive compound retention using response surface methodology - Karatas, Mukaddes (Elsevier, 2025)
This study investigates the effects of drying temperature (40-60 degrees C), drying time (11-15 h), and air velocity (1.5-2.5 m/s) on the moisture ratio (MR), effective moisture diffusivity (D-eff), total phenolic content (TPC), and radical scavenging activity (RSA) of pomegranate slices during hot air drying. Response surface methodology was used to model and optimize the process. Drying temperature significantly influenced MR (p < 0.0001), followed by time (p < 0.0001) and air velocity (p < 0.05). D-eff ranged from 1.21 x 10(-10) to 1.79 x 10(-10) m(2)/s and was primarily affected by temperature. TPC (630.12-745.89 mg GAE/100 g dw) and RSA (33.4-41.2 %) were significantly impacted by both temperature and time. Key interactions were observed, particularly between temperature and time (p = 0.0043 for MR; p = 0.0001 for TPC). Optimal conditions were 60 degrees C, 13 h, and 1.5 m/s, yielding MR of 0.14, Deff of 1.79 x 10(-10) m(2)/s, TPC of 745.89 mg GAE/100 g dw, and RSA of 41.2 %, with a desirability score of 0.873. These results provide a basis for improving drying processes to preserve quality and bioactivity, with potential applications in food and nutraceutical industries.
Keywords: Pomegranate slices; Convective drying; RSM; Bioactive compound; Moisture ratio; Process optimization